Impact of Learning Motivation and Physical Condition on Physical Education Learning Outcomes in Junior High School Students Aged 13-15 Years: A Analysis studies - Fikri, Muhammad; Nofrizal, Dedi; Nugroho, Agung; Lubis, Hafiz Yazid (INSPIREE: Indonesian Sport Innovation Review, 2024)
The  purpose  of  the study. to determine and evaluate the relative contributions of physical fitness and learning motivation to the learning outcomes of students in the 7–9 age range. Materials and methods. The purpose of correlation approaches is to quantitatively ascertain if and to what extent two or more variables are correlated. Data is analyzed using the statistical techniques of correlation and multiple regression utilizing the SPSS (Statistical Product and Service Solution Version 25) software. Before the advent of statistical methods for hypothesis testing. Use the Kolmogorov-Smirnov test (uji K-S) to check for data normality. Results. The coefficient of correlation for rx12y = 0.49 is indicated. Koefisisen korelasi signifikansi diperoleh F hitung 4,37>t tabel 3,35, dengan distribusi t dengan α = 0,05 dan k = 2 sebagai pembilang dan (n–k–1) sebagai dk penyebut. In other words, there is a positive correlation between the Jasmani Motivasi Belajar and the Penjasorkes Learning Outcomes, which are 0,492 x 100%, or 0,24 x 100%, or 24%. Conclusions. Students' willingness and excitement to participate in physical education learning activities will be influenced by their motivation for learning. A learner who understands effective learning motivation would attempt to inspire themself to learn well. Since achieving satisfactory learning outcomes is one of the goals of the processes and activities that take place in the classroom, teachers are crucial in helping students develop motivation for learning and improving their physical fitness.